(untitled) (KASBIT Business Journal, 2023)
This study examines the impact of product attributes on re-purchase intention and customer satisfaction, store attributes on re-purchase intention and customer satisfaction, and customer satisfaction on re-purchase intention. The postulated hypothesis of this study reveals that product and store characteristics positively impact customer satisfaction and re-purchase intention. Moreover, customer satisfaction positively impacts customers’ re-purchase intention. Directors in the FMCG business may learn a lot about how to serve their customers better and how to reap more advantages from their current clientele by taking into account the feedback of FMCG customers. This research shows that the re-purchase intention is high if a product’s attributes appeal to Pakistani FMCG customers. Customers may be nudged toward the post-purchase goal of an esteem-included product, and this analysis acknowledges the role of store attributes. Additionally, the study shows that customer loyalty drives the connection between item attributes and post-purchase as the go-between in FMCG. Customer loyalty similarly influences the relationship between shop qualities and post-purchase intention. Finally, this investigation provides future directions for managers in fostering client loyalty, which may prevent them from losing customers to rival fast-moving customer goods (FMCG) companies offering comparable products and services